Reflections on the constraints of applying information literacy in the Algerian university - GHIAT , Boufeldja (Journal of Human Sciences, 2021)
Despite the efforts made by the Algerian University, for the improvement of the quality of training, the results remain meager, and fail to keep up with scientific and educational progress taking place elsewhere in the world. The Algerian university has several constraints to apply information culture. These include the abilities and attitudes of teachers and students, library conditions and computer resources. While material and educational resources can be acquired, the most important thing is the adoption of an information culture of education strategy. Much work remains to be done to gather the necessary resources, in terms of computer tools, reorganization of libraries, and educational training of university lecturers.